NATURE AS MONSTER OF TERROR: RE-READING ROMA TEARNE’S MOSQUITO THROUGH ECO-GOTHIC THEORY - Haq, Naeemul (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper aims to study Sri Lankan English writer Roma Tearne’s novel Mosquito (2007)—as EcoGothic texts that use gothicised landscape tropes of the sea, the forest, the beach to highlight the intersections between human exploitation and environmental degradation in post-colonial Sri Lanka. By drawing on the theories of the EcoGothic and associated concepts such as Ecophobia, I examine how the EcoGothic is manifested in this novel through a close connection between nature and the (dark) history of a place immersed in terrorism and civil war. The paper argues that Mosquito portrays how the civil war turned nature into a location of monstrosity. The use to which certain landscapes are put in post-colonial Sri Lanka during the civil war creates an ecophobic narrative about them. Through the EcoGothic, Tearne in her novel overturns popular conceptions of tropical islands as idyllic and shows these landscapes as sites of fear and the uncanny, and as palimpsests of multiple histories of political and ecological violence. It highlights how the use to which certain landscapes are put in post-colonial Sri Lanka renders these spaces fearful and uncanny, generating ecophobia.